PENGARUH EFEKTIVITAS KOMUNIKATOR/NARASUMBER TERHADAP PENGETAHUAN APARATUR DESA/KELURAHAN DI KOTA AMBON - Buamona, Idrus; Murliasari, Rikha (Jurnal Politik Pemerintahan Dharma Praja, 2017)
ABSTRACT The purpose of this study was to determine how much influence the credibility of communicators/informant on Knowledge Level Government Apparatus Village/Sub, how much influence Logic Design Links to the Knowledge Level Government Apparatus Village/ Sub, and how much influence the credibility of the communicator/Informant and Logic Design Book the level of Government Personnel Knowledge Village/Sub. This type of research used in this research is quantitative research eksplanatif which depict or describe a problem that the results are generalizable. Quantitative eksplanatif. The result of this research is that there is a direct influence simultaneously between variables Credibility Communicators and Design Links to the Knowledge Level of 0,260 or 26%, which implies that the influence of independent variables (credibility and message design) on the dependent variable (the level of knowledge) is approximately 26%. With high credibility communicator/resource will be easily trusted by the communicant. Keywords: credibility; communicators/speaker; knowledge